Investigation of the effect of dipyrone on cells isolated from intervertebral disc tissue - Akgun, Feride Sinem (Exp Ther Med, 2019)
The present study aimed to evaluate the effects of dipyrone, an indispensable analgesic, anti-pyretic and anti-spasmodic used in emergency departments, on nucleus pulposus and annulus fibrosus cells in vitro. After surgical biopsy, primary cell cultures were prepared from intact intervertebral disc tissues. Dipyrone was administered to the cultures in the experimental groups except for the control group. The data obtained were statistically evaluated. The proliferation was identified to be suppressed via MTT analysis. The gene expression profile of the intervertebral disc cells in the dipyrone-treated groups was significantly changed. The expression of chondroadherin, cartilage oligo matrix protein, interleukin-1β and metalloproteinase (MMP)-19 genes were decreased, but MMP-13 and MMP-7 genes expressions were increased, as determined via reverse transcription-quantitative PCR. AO/PI staining revealed that no apoptotic or other type of cell death was detectable after administration of dipyrone does not mean that the drug is innocuous. The occurrence of cellular senescence and/or the halt of cell proliferation may also be important mechanisms underlying the adverse inhibitory effects of dipyrone. Therefore, prior to administering dipyrone in clinical practice, all possible adverse effects of this drug should be considered.